PUSTAKAWAN MASA DEPAN DAN PENGEMBANGAN TEKNOLOGI INFORMASI - Daryono Daryono (Central Library of Universitas Sebelas Maret, 2016)
The purpose of this paper is to determine the motivating librarians to improve theirability in applying information technology in libraries and improve the professionalismand add insight to the writer in particular and librarians in general. The problemsare studied in this paper is how much the role of librarians in applying informationtechnology in libraries, how the attitude of librarians to the presence of informationtechnology, as well as how to apply the ability of information systems librarian at theLibrary, as well as the obstacles encountered in applying information technology inlibraries. The method of writing in this paper uses methods of literature by combiningsome of the opinions of experts in the field of library science, analyzed and thenbe concluded. The conclusion of this paper is the Librarian as future informationprofessionals have a variety of challenges and obstacles in applying informationtechnology in libraries, among others: 1) Increasing new profession, 2). Shiftingthe role of libraries, 3). Digitalization of Information, and 4). Paradigm Changes inlibrary services. So to deal with future librarians must have the pioneer spirit, whichis critical in the development of information technology, and are able to apply it in thelibrary development. Librarians will have a very important role in the development ofinformation systems in the library, because in the future, the librarian will collaboratewith a variety of background knowledge resources in various formats and forms.Librarians will also collaborate in the long term and short passes boundaries of spaceand time.